The true merits of the controversy in Arkansas, for the consideration of honest men. - Pike & Johnson (Washington, 1874)
Relates to the contest of Joseph Brooks and Elisha Baxter for the governorship of Arkansas.
Also available in digital form on the Internet Archive Web site.
Keywords: Brooks-Baxter War, Ark., 1874.; Arkansas -- Politics and government; Brooks, Joseph, -- 1821-1877.; Baxter, Elisha, -- 1827-1899.; Brooks-Baxter War, Ark., 1874.